IMPLEMENTASI PROGRAM LAYANAN RAKYAT UNTUK SERTIFIKAT TANAH (LARASITA) DI KABUPATEN KUBU RAYA - DORINA HARTANIA, SH. A2021141097, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis discusses the People's Programme Implementation Service for Land Certificate (Larasita) Di Kubu Raya. Normative-sociological research. This study aims to provide reveal and analyze the effectiveness of the program socialization Larasita by Kubu Raya District Land Office to the improvement of land services. From the research we concluded that implementation of the policy program of the Kubu Raya Larasita in which the author in view the success or failure of a policy can be viewed from three aspects: the organization, interpretation and application. Furthermore, the factors that have been influential in the implementation of program policies Larasita in Kubu Raya, namely Communications (Communications), Resources (resources), Attitude (dispositions or attitudes) and Bureaucratic Structure (bureucratic structure). From the research we concluded that implementation of the policy program of the Kubu Raya Larasita in which the author in view the success or failure of a policy can be viewed from three aspects: the organization, interpretation and application. Furthermore, the factors that have been influential in the implementation of program policies Larasita in Kubu Raya, namely Communications (Communications), Resources (resources), Attitude (dispositions or attitudes) and Bureaucratic Structure (bureucratic structure). Of the four factors is the author breaks into two factors supporting and hindering the implementation of the policy program Larasita in Kubu Raya is a supporting factor composed of bureaucratic structures where the factor that fundamentally support the implementation of program policies Larasita in Kubu Raya because in terms of standard operational procedure (SOP) clearly through Per Ka BPN Decree No. 4 of 2006 stated clearly describes in detail the organizational structure and standard operational procedure (SOP) of the District Land Office / City throughout Indonesia and supported again by Per Ka BPN Decree No. 18 Year 2009 on Larasita, and in terms of fragmentation, where the implementation of the policy program in Kubu Raya Larasita less memerluakan coordination so vast. Another factor is the limiting factor, namely Communications (Communications), Communication is a factor that causes the ineffectiveness of policy implementation program Larasita in Kubu Raya due to a lack of consistency or uniformity of the size of the basis and purpose of the policy program Larasita communicated with less well in Kubu Raya. Yag second is Resources (resources), the resource is a second factor that led to the policy program Larasita in Kubu Raya effective in its implementation because the components contained in resources such as the number of staff, the expertise of the executive is fairly mediocre, the missing information so relevant, as well as the lack of support facilities that can be used to carry out program activities. The latter is the attitude (dispositions or attitudes), attitude or disposition also a factor in less support the implementation of program policies Larasita in Kubu Raya as the implementor does not seem serious in melaksnakan program policies Larasita in the region Kababupaten Kubu Raya because during the socialization program Larasita only included the socialization of other programs that are owned by the District Land Office Kubu Raya as an example Prona.Keywords: Implementation, Program Service of the People, the Land Certificate.ABSTRAKTesis ini Membahas Implementasi Program Layanan Rakyat Untuk Sertifikat Tanah (Larasita) Di Kabupaten Kubu Raya. Penelitian bersifat normatif-sosiologis. Penelitian ini bertujuan memberikan2Mengungkapkan dan menganalisis efektifitas pelaksanaan sosialisasi program larasita oleh Kantor Pertanahan Kabupaten Kubu Raya terhadap peningkatan pelayanan pertanahan. Dari hasil penelitian diperoleh kesimpulan bahwa Pelaksanaan dari pada kebijakan program Larasita di Kabupaten Kubu Raya yang mana penulis dalam melihat berhasil tidaknya suatu kebijakan dapat dilihat dari tiga aspek yaitu organisasi, interpretasi dan aplikasi. Selanjutnya mengenai faktor-faktor yang selama ini berpengaruh di dalam pelaksanaan kebijakan program larasita di Kabupaten Kubu Raya, yaitu Komunikasi (Communications), Sumber Daya (resources), Sikap (dispositions atau attitudes) dan Struktur Birokrasi (bureucratic structure). Dari keempat faktor inilah penulis mengelompokkannya menjadi dua yaitu faktor pendukung dan penghambat pelaksanaan dari kebijakan program Larasita di Kabupaten Kubu Raya yaitu faktor pendukung yang terdiri dari struktur birokrasi yang mana faktor yang secara mendasar mendukung pelaksanaan kebijakan program Larasita di Kabupaten Kubu Raya karena dari segi standard operational procedure (SOP) yang secara jelas melalui Per Ka BPN RI No 4 Tahun 2006 tertera secara jelas menjelaskan secara rinci struktur organisasi dan standard operational procedure (SOP) dari Kantor Pertanahan Kabupaten/Kota seluruh Indonesia dan ditunjang lagi dengan Per Ka BPN RI No 18 Tahun 2009 tentang Larasita, dan dari segi fragmentasi, dimana pelaksanaan dari pada kebijakan program larasita di Kabupaten Kubu Raya kurang memerluakan koordinasi yang begitu luas. Faktor lain yaitu faktor penghambat yaitu Komunikasi (Communications), Komunikasi merupakan faktor yang menjadi penyebab ketidak-efektifan pelaksanaan kebijakan program Larasita di Kabupaten Kubu Raya karena kurangnya konsistensi atau keseragaman dari pada ukuran dasar dan tujuan dari program kebijakan larasita yang dikomunikasikan dengan kurang begitu baik di Kabupaten Kubu Raya. Yag kedua adalah Sumberdaya (resources), sumberdaya merupakan faktor kedua yang menyebabkan kebijakan program larasita di Kabupaten Kubu Raya efektif dalam pelaksanaannya karena komponen-komponen yang terkandung didalam sumberdaya seperti jumlah staf, keahlian dari para pelaksana yang terbilang pas-pasan, informasi yang kurang begitu relevan, serta kurangnya fasilitas-fasilitas pendukung yang dapat dipakai untuk melakukan kegiatan program. Yang terakhir adalah Sikap (dispositions atau attitudes), sikap atau disposisi juga merupakan faktor kurang mendukung pelaksanaan kebijakan program larasita di Kabupaten Kubu Raya karena para implementor terlihat tidak serius dalam melaksnakan kebijakan program larasita di wilayah Kababupaten Kubu Raya karena selama ini sosialisasi program larasita hanya diikutkan pada sosialisasi program-program lain yang dimiliki oleh Kantor Pertanahan Kabupaten Kabupaten Kubu Raya seperti contohnya prona.Kata Kunci: Implementasi, Program Layanan Rakyat, Sertifikat Tanah.